PENGEMBANGAN STRATEGI DESAIN UNTUK MENINGKATKAN PESEPEDA KOMUTER DIKOTA BANDUNG - Romadhoni, Bobby; Soewardikoen, Didit Widiatmoko; Swasty, Wirania (Universitas Mercu Buana, 2023)
In 2023, there will be a phenomenon in the city of Bandung, namely that the number of vehicles is almost the same as the population, causing congestion and increased pollution levels which often occur on roads during commuter trips at times when vehicle volume is very dense, namely in the morning and evening. The existence of alternative transportation, namely bicycles, could be the answer to this phenomenon. However, there is a phenomenon that the number of cyclists in the city of Bandung is decreasing, especially for commuters. By looking at this potential, this research discusses design strategies for commuter cyclists with a case study in the city of Bandung. This research is a qualitative and quantitative research in the field of design to analyze cyclists commuting by bicycle by documenting visual samples as image aspect data, interviews with the creator aspect and questionnaires to consumers as the viewer aspect. Data obtained from various data collection methods is then analyzed using design strategies looking at internal and external factors. The results of this research will answer design strategies for commuter cyclists with a case study in the city of Bandung. Through this research, it is hoped that it can become a guide that makes it easier for people to commute on bicycles in the city of Bandung.